2022
DOI: 10.1007/s00018-022-04191-8
|View full text |Cite
|
Sign up to set email alerts
|

Ubr1-induced selective endophagy/autophagy protects against the endosomal and Ca2+-induced proteostasis disease stress

Abstract: The cellular defense mechanisms against cumulative endo-lysosomal stress remain incompletely understood. Here, we identify Ubr1 as a protein quality control (QC) E3 ubiquitin-ligase that counteracts proteostasis stresses by facilitating endosomal cargo-selective autophagy for lysosomal degradation. Astrocyte regulatory cluster membrane protein MLC1 mutations cause endosomal compartment stress by fusion and enlargement. Partial lysosomal clearance of mutant endosomal MLC1 is accomplished by the endosomal QC ubi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 93 publications
1
7
0
Order By: Relevance
“…Many organelles are selectively targeted for macroautophagy via compartment-specific receptors (Lamark and Johansen, 2021), but such a process has not been specifically described for neuronal endosomes/MVEs. Our data suggest that synapses use a proteostatic mechanism called endosomophagy or simaphagy that has been previously observed in cell culture (Migliano et al, 2023;Millarte et al, 2022;Wang et al, 2022;Zellner et al, 2021), adding to the numerous intersections between endolysosomal traffic and autophagy in neurons (Boecker and Holzbaur, 2019). We found that autophagy is induced in ESCRT mutant synapses, presumably to dispose of aberrant endosomes, with different outcomes in Tsg101 KD versus Hrs mutants: Tsg101 KD led to aberrant autophagic vacuoles and reduced autophagic flux, perhaps due to a secondary role for ESCRT-1/Tsg101 in phagophore closure or another step of autophagy (Takahashi et al, 2018).…”
Section: Other Synaptic Functions Of Escrtsupporting
confidence: 80%
See 1 more Smart Citation
“…Many organelles are selectively targeted for macroautophagy via compartment-specific receptors (Lamark and Johansen, 2021), but such a process has not been specifically described for neuronal endosomes/MVEs. Our data suggest that synapses use a proteostatic mechanism called endosomophagy or simaphagy that has been previously observed in cell culture (Migliano et al, 2023;Millarte et al, 2022;Wang et al, 2022;Zellner et al, 2021), adding to the numerous intersections between endolysosomal traffic and autophagy in neurons (Boecker and Holzbaur, 2019). We found that autophagy is induced in ESCRT mutant synapses, presumably to dispose of aberrant endosomes, with different outcomes in Tsg101 KD versus Hrs mutants: Tsg101 KD led to aberrant autophagic vacuoles and reduced autophagic flux, perhaps due to a secondary role for ESCRT-1/Tsg101 in phagophore closure or another step of autophagy (Takahashi et al, 2018).…”
Section: Other Synaptic Functions Of Escrtsupporting
confidence: 80%
“…Our data also raise the possibility of a novel synaptic proteostasis mechanism which might be termed "endosomophagy", as has been seen in cell culture (Millarte et al, 2022;Wang et al, 2022;Zellner et al, 2021), and adds to the numerous intersections between endolysosomal traffic and autophagy in neurons (Boecker and Holzbaur, 2019). Many organelles are selectively targeted for macroautophagy via compartment-specific receptors (Lamark and Johansen, 2021), but such a process has not been specifically described for neuronal endosomes/MVEs.…”
Section: Other Synaptic Functions Of Escrtmentioning
confidence: 70%
“…In SCI, the repair of autophagic flux or activation of autophagy reduces neuronal inflammation, apoptosis, and pyroptosis ( Rong et al, 2019 ; Zhou et al, 2020 ; Wu et al, 2021 ; Huang et al, 2022 ). UBR1 also has the potential to regulate autophagy and mitophagy ( Yamano and Youle, 2013 ; B.B. Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ubiquitination and autophagy, two predominant intracellular degradation pathways, are distinct in their mechanisms but inextricably connected in controlling protein quality and maintaining cellular homeostasis ( P. Liu et al, 2022 ). A recently published article demonstrated that UBR1 facilitates the clearance of misfolded MLC1 during Ca 2+ stress by eliciting p62-mediated selective autophagy ( B.B. Wang et al, 2022 ), which prompted the authors to investigate whether UBR1 is linked to autophagy dysregulation in SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling routes of proteostasis and inflammation are carefully controlled by changes in temporal and spatial distribution of intracellular free Ca 2+ ( 16 , 17 , 18 , 19 , 20 ). Generally, the increase in intracellular Ca 2+ concentration can occur via two pathways: Ca 2+ is released from intracellular stores or it travels through plasma membrane Ca 2+ channels into the cytosol ( 21 ).…”
mentioning
confidence: 99%